Produksi Jagung dan Umbi-Umbian, dan Peranannya dalam Perekonomian Indonesia - Juri Juswadi; Pandu Sumarna; Neneng Sri Mulyati (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
This study aims to determine the performance of Indonesian maize and tuber production and forward linkages with the agro-industry sector. Through this research it can be seen the role of maize and tuber commodities in the Indonesian economy. The results showed that corn production increased by 91.24% during the period 2000-2013, with an average growth of 5.22% per year. Tuber production consisting of cassava increased by 27.44% over the period 2000-2013 with an average growth of 2.91% per year, and sweet potatoes increased by 30.59% with an average of 2.18% per year. The domestic output of the corn sector increased from Rp. 855,554 million in 1985 to Rp. 74,817,036 million in 2008 and the tuber sector increased from Rp. 1,798,023 million in 2000 to Rp. 29,209,547 million in 2008. Transactions in the corn sector line and tubers showed a significant increase during the 1985-2008 period, from six transactions to 14 transactions. An increase in the forward linkages between the corn sector and the agro-industry sector from 0.188 to 0.258 in the period 2005-2008, showed an increase in the contribution of the corn sector as an intermediate input for the agro-industry sectors, while in the tuber sector there was no increase.